Rutter's Child and Adolescent Psychiatry: Fifth Edition - Rutter, M; Bishop, D; Pine, D; Scott, S; Stevenson, J; Taylor, E; Thapar, A (Blackwell Publishing Ltd., 2009)
Rutter's Child and Adolescent Psychiatry has become an established and accepted textbook of child psychiatry. Now completely revised and updated, the fifth edition provides a coherent appraisal of the current state of the field to help trainee and practising clinicians in their daily work. It is distinctive in being both interdisciplinary and international, in its integration of science and clinical practice, and in its practical discussion of how researchers and practitioners need to think about conflicting or uncertain findings. This new edition now offers an entirely new section on conceptual approaches, and several new chapters, including: neurochemistry and basic pharmacology brain imaging health economics psychopathology in refugees and asylum seekers bipolar disorder attachment disorders statistical methods for clinicians This leading textbook provides an accurate and comprehensive account of current knowledge, through the integration of empirical findings with clinical experience and practice, and is essential reading for professionals working in the field of child and adolescent mental health, and clinicians working in general practice and community pediatric settings. © 2008 Blackwell Publishing Ltd.